Gulf Cooperation Council Energy Sectors Governance and Dividend Policy - Awwad, Bahaa Sobhi AbdeLatif; Hamdan, Allam Mohammed Mousa (International Journal of Economics and Financial Issues, 2018)
This study is aims to investigate the governance of the most important sector in the Gulf financial markets, energy sectors. It also looks into the effect of corporate governance on one of the most significant financial polices of in organizations, which is dividend policy. This study involves a sample of eight energy firms in a ten years' time series, 2008 to 2017. These firms were selected from six Gulf financial markets: Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and United Arab Emirates. The corporate governance was measured by using four indicators. Whereas, the dividend policy was expressed by payout ratio. The findings of the study showed that the outcome hypothesis is adopted in the Gulf Cooperation Council GCC energy sectors; the companies with good governance seek to distribute the profits among shareholders to reduce the conflict of interests and reduce the agency costs. The results also indicated a positive role of public governance in the relationship between corporate governance and the dividend policy. Keywords: GCC energy sectors; Governance; Dividends policy; GCC Financial Markets, Agency Theory JEL Classifications: D53, G3